Performance of Data Services in Cellular CDMA in Presence of Soft Handoff and Packet Combining - S. D. Roy; S. Kundu (Radioengineering, 2010)
Performance analysis of data services is studied in CDMA network in presence of soft handoff (HO) and packet combining. Packet combining in conjunction with soft handoff is found to enhance throughput, reduce delay and packet delay variation (PDV) significantly. A stop and wait automatic repeat request (ARQ) scheme has been assumed. Two different packet combining schemes for packet data service, one based on log likelihood ratio (LLR) and another based on equal gain combining (EGC) have been studied. A cross layer interactions between ARQ and packet combining at link layer and soft HO in physical layer has been shown.